E-Certificate Policy in Equivalency Education: Opportunities, Challenges, and Its Impact on the Recognition of Non-Formal Graduates in Indonesia - Afriani, Zurmi; Haryanto, Fepi Trimunir (Journal Governance Bureaucratic Review, 2026)
Equivalency education plays an important role in Indonesia’s national education system by providing alternative learning pathways for citizens who are unable to complete formal schooling through regular educational routes. However, graduates of non-formal education, particularly those from Paket A, Paket B, and Paket C, still face challenges related to certificate recognition, administrative verification, public trust, and acceptance by higher education institutions, employers, and public agencies. In response to these issues, the e-certificate policy has emerged as a significant instrument for strengthening the credibility, authenticity, and portability of educational credentials in the digital era. This study aims to analyze the opportunities, challenges, and impacts of e-certificate policy on the recognition of non-formal education graduates in Indonesia. The research employed a qualitative approach using secondary data analysis. Data were collected from regulations, government policy documents, institutional reports, scholarly articles, and relevant literature on digital credentials, equivalency education, and educational recognition. The data were analyzed through document review and content analysis by identifying regulatory foundations, institutional mechanisms, implementation challenges, and recognition outcomes. The findings show that e-certificate policy offers several opportunities, including faster certificate issuance, easier digital verification, reduced document falsification, improved administrative efficiency, and stronger institutional trust in non-formal education credentials. Nevertheless, the policy also faces challenges related to unequal digital infrastructure, limited institutional readiness, data protection risks, inconsistent recognition across sectors, and the continuing social stigma toward equivalency education graduates.